Factors affecting female college students’ intention to use digital technology in wearable devices to stimulate health monitoringSummary Table - Grace Donghee Shin; Wookyoung Jeong; Hye-Eun Lee (Heliyon, 2023)
In this study, we measured female college students' mental health and physical activities to identify factors that affect their intention to use wearable health-monitoring devices. Specifically, the study derived correlations between female students' health-related quality of life (HRQoL) including, physical activity, stress level, attitudes toward eating, and self-esteem. Using this information, we ascertained the relationship between female college students’ use of wearable devices and physical activity and examined the requirements for smartphone applications for healthcare. We collected data from 308 female college students in the Republic of Korea over four months starting in July 2021 using an anonymous online survey. We then analyzed the data using descriptive statistics and linear regression. The results showed that the factors that caused stress in female college students during the past six months were fatigue, COVID-19, grades, worries about getting a full-time job, menstruation, and being overweight. This paper found a negative correlation between stress and self-esteem and a positive correlation between physical activity and self-esteem. People with experience using wearable devices reported a higher intensity in physical activity. More than half the participants recorded biometric information for their menstrual cycles and menstrual cramps regardless of whether they were using wearable devices. Currently, healthcare applications can suggest diets and track nutritional intake, menstrual cycles, and amount of exercise, which users want simultaneously. Therefore, there is a market demand for a mobile application linked with a wearable device and tailored for female college students that could combine and manage all these data. In the future, application developers should consider the needs of female college students.